PENGARUH KOMPENSASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT HASWARPIN GROUP - Nurmaijurah, Nurmaijurah; Siringoringo, Renniwaty (LPPM Universitas Putera Batam, 2019)
This study aims to know empirically the direct influence and influence of the variables of compensation, work discipline and employee performance simultaneously. This study used 111 employees at PT. Haswarpin Group as a research sample. The data obtained were analyzed using multiple linear regression analysis with the help of SPSS 20 statistical software. The results of this study are: compensation has a positive and significant effect on employee performance and work discipline has a positive and significant effect on employee performance and compensation and work discipline simultaneously has a positive effect and significant to employee performance.